Dystocia due to hydrocephalic monster in a local cow - SOBTI, D K; PANDIT, R K (The Indian Journal of Animal Reproduction, 2023)
Dystocia due to congenital hydrocephalic monster has been reported in a pluriparous local cow.
Keywords: Treatment; dystocia; hydrocephalus; congenital; cow